Do we need cardiopulmonary exercise to determine the optimal time for intervention in valvular heart disease?. (25th November 2020) - Cortina, C; Sarrion, M; Beltran, C; Suberviola, V; Sanchez, A; Mora, L; Estevez, A; Briongos, S; Vaqueriza, D; Dominguez, M; Munoz Aguilera, R
Abstract: Introduction: Cardiopulmonary exercise testing (CPET) is underused in many clinical conditions other than HF. In valvular heart disease (VHD), CEPT can aid in choosing the right timing for surgery. The goals of this study were to compare the assessment of functional capacity (FC) by CEPT and NYHA scale, and to analyze the relationship between ventilatory efficiency (VE) parameters and time to surgery. Methods: 197 CPET were performed in 163 patients with moderate or severe VHD (51% female). Real METS (RM) were calculated as indexed peak VO2/3.5 (1 MET = 3.5 ml O2/kg/min) and compared to estimated METS (EM) derived by the exercise duration. An agreement analysis between RM, EM and NYHA was performed. The association among VE/VCO2 slope, pet CO2 at anaerobic threshold (AT), OUES and time to surgical indication was also studied using Cox logistic regression analysis. Results: See Table. The RM and EM were 4, 7±1, 7and 6, 2±2, 9, respectively (p<0.01), and the correlation was low (ICC=0, 7, p<0.001). The agreement between NYHA class and % of peak predicted V02 was very low (kappa index = 0.1, p<0.001). VE parameters were predictive of an earlier surgical indication: petCO2 AT (p=0.02), VE/VCO2 slope (p=0.069), OUES (p=0.014). Conclusions: In asymptomatic VHD patients, the surgical indication should not rely solely in their FC assessed by either NYHA scale or EM derived by duration of exercise. In our series, these parameters clearly overestimated the FC of the population. Also, the ventilatory inefficiency may be a surrogate marker of advanced disease and lead to a closer surveillance for an earlier intervention. Funding Acknowledgement: Type of funding source: None